Lipids and phenylketonuria: current evidences pointed the need for lipidomics studies - Guerra, Inês M. S. (2021)
Phenylketonuria (PKU) is the most prevalent inborn error of amino acid metabolism. The disease is due to the deficiency of phenylalanine (Phe) hydroxylase activity, which causes the accumulation of Phe. Early diagnosis through neonatal screening is essential for early treatment implementation, avoiding cognitive impairment and other irreversible sequelae. Treatment is based on Phe restriction in the diet that should be maintained throughout life. High dietary restrictions can lead to imbalances in specific nutrients, notably lipids. Previous studies in PKU patients revealed changes in levels of plasma/serum lipoprotein lipids, as well as in fatty acid profile of plasma and red blood cells. Most studies showed a decrease in important polyunsaturated fatty acids, namely DHA (22:6n-3), AA (20:4n-6) and EPA (20:5n-6). Increased oxidative stress and subsequent lipid peroxidation have also been observed in PKU. Despite the evidences that the lipid profile is changed in PKU patients, more studies are needed to understand in detail how lipidome is affected. As highlighted in this review, mass spectrometry-based lipidomics is a promising approach to evaluate the effect of the diet restrictions on lipid metabolism in PKU patients, monitor their outcome, namely concerning the risk for other chronic diseases, and find possible prognosis biomarkers.